The influence of extinction and counterconditioning procedures on operant evaluative conditioning and intersecting regularity effects. Issue 10 (7th October 2020) - Hughes, Sean; Mattavelli, Simone; Hussey, Ian; De Houwer, Jan
Abstract : One of the most effective methods of influencing what people like and dislike is to expose them to systematic patterns (or 'regularities') in the environment, such as the repeated presentation of a single stimulus (mere exposure), two or more stimuli (evaluative conditioning (EC)) or to relationships between stimuli and behaviour (approach/avoidance). Hughes et al . (2016) J. Exp. Psychol. Gen. 145, 731–754. (doi:10.1037/xge0000100 ) found that evaluations also emerge when regularities in the environment intersect with one another. In this paper, we examined if evaluations established via operant EC and intersecting regularities can be undermined via extinction or revised via counterconditioning. Across seven pre-registered studies ( n = 1071), participants first completed a learning phase designed to establish novel evaluations followed by one of multiple forms of extinction or counterconditioning procedures designed to undo them. Results indicate that evaluations were— in general —resistant to extinction and counterconditioning. Theoretical and practical implications along with future directions are discussed.